Music genre recognition using Deep Learning - Roy, Arpita; Parveen, Nikhat; Saxena, Surabhi; Sasidhar, Talasila (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents a convolutional intermittent neural system (CRNN) for music labeling. CRNNs exploit convolutional neural systems (CNNs) for nearby element extraction and recurrent neural systems (RNNs) for fleeting summarisation of the extricated highlights. We contrast CRNN and two CNN structures that have been utilized for music labeling while at the same time controlling the quantity of parameters as for their presentation and preparing time per test. Generally, we found that CRNNs show solid execution as for the quantity of parameter and preparing time, demonstrating the viability of its cross-breed structure in music highlight extraction and highlight summarisation